2014
DOI: 10.1080/03075079.2014.988702
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate work placements: an analysis of the effects on career progression

Abstract: Undergraduate work placements: an analysis of the effects on career progressionCombining work experience with degree-level study is seen as a key differentiator for securing employment upon graduation in a competitive employment market. The positive benefits of sandwich courses, where up to twelve months is spent working in industry, are widely acknowledged in academic literature though data analysis tends to focus on cohorts in single subject areas with course-based factors possibly influencing outcomes. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 32 publications
7
90
1
1
Order By: Relevance
“…This is in line with studies showing that the more hours the students work, the more negative the effect on their grades is (Callender 2008;Bradley 2006). The present study did not confirm previous research showing that work experience within a student's study field was related to a higher grade (Wang et al 2010;Brooks and Youngson 2014). Moreover, some studies have found no relationship between working and grades (Sulaiman and Mohezar 2006;Nonis and Hudson 2006).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This is in line with studies showing that the more hours the students work, the more negative the effect on their grades is (Callender 2008;Bradley 2006). The present study did not confirm previous research showing that work experience within a student's study field was related to a higher grade (Wang et al 2010;Brooks and Youngson 2014). Moreover, some studies have found no relationship between working and grades (Sulaiman and Mohezar 2006;Nonis and Hudson 2006).…”
Section: Discussionsupporting
confidence: 65%
“…Empirical evidence exists of work experience related to one's own academic field increasing students' grade point average (Wang et al 2010). Similar results have been found in research concerning internship (Brooks and Youngson 2014;Patel et al 2012). However, it has also been found that working students achieved lower grades than non-working students (Hunt et al 2004;Salamonson et al 2012).…”
Section: Introductionsupporting
confidence: 61%
“…Students gain relevant and paid employment whilst employers seek commitment, communication skills and specific aptitudes pertaining to degree type. Students who have taken a placement are at a distinct advantage over students who have not when applying for work after graduation [12]. Employers benefit from student placement too.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Brooks and Youngson [12] suggest students do not see future remuneration in placements, 'long term benefits are not always appreciated with fewer students engaging in the process'. Lowden reports upon the high expectations of the employer, 'graduates need to demonstrate a range of skills and attributes that include team working, communication, leadership, critical thinking, problem solving and often managerial abilities or potential' [14].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, there is a competition for the most skilled professionals in the computing and software engineering job market. Work placements have been shown to be beneficial to careers after graduation [1] and learning about the industry affects the students' career choices [10]. Permission to make digital or hard copies of part or all of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%